The Effectiveness of The Bankruptcy Prediction Indicators Approach From the Johannesburg Stock Exchange Perspective - Cassim, Ronel Juliana (The Indonesian Journal of Accounting Research, 2025)
Abstract: Bankruptcy has many fatalities and results in significant losses, so early detection of financial difficulties is essential. This study compares the bankruptcy prediction indicators approach (BPIA) with the emerging market score (EMS) as a benchmarking measure to evaluate BPIA's ability to predict bankruptcy. The study aims to determine whether the BPIA is a reliable predictor of company failure. A quantitative research approach was adopted, analyzing data from ten South African companies delisted from the Johannesburg Stock Exchange (JSE) across seven different sectors, obtained through purposive sampling and sourced from the Inet BFA McGregor database from 2017 to 2021. The empirical test results demonstrate that the BPIA is a reliable bankruptcy prediction tool, capable of detecting financial failure up to five years in advance. The results highlight the BPIA's 100% accuracy in predicting South African corporate bankruptcy, outperforming the EMS model. This study could help academics, financial professionals, government officials, managers, practitioners, shareholders, and other stakeholders. The recommendation of this study is to integrate the BPIA approach into companies' annual financial reporting.